Social Impacts of Work Integration Social Enterprise in Hong Kong – Workfare and Beyond. Issue 2 (4th May 2019) - Leung, Zeno C. S.; Ho, Amy P. Y.; Tjia, Linda Y. N.; Tam, Raymond K. Y.; Chan, K. T.; Lai, Michael K. W.
Abstract: In 2017, there are over six hundreds social enterprises in Hong Kong. Among them, approximately 70% are work integration social enterprises (WISEs) primarily aiming at creating employment and/or providing vocational training for the disadvantaged groups. Impact assessment of these WISEs is a growing concern in the society. In this article, the authors review major types of impact assessment approaches and three categories are delineated – outcome-based, structured-based and process-based approaches. Through the application of one particular outcome-based approach, Social Return on Investment (SROI), onto four invited local WISEs, the social impacts induced by selected WISEs and their significances are discussed.